The Psalms as Christian praise : a historical commentary - Waltke, Bruce K.; Houston, J. M. (James Macintosh), 1922- (2019)
"Completes a trilogy of exegetical volumes on the Psalms, following up on The Psalms as Christian Worship and The Psalms as Christian Lament. Examines twelve praise psalms, each including a translation, commentary, and how the psalm was interpreted in the Christian tradition. Intended especially for preachers and students of Psalms"--
The Psalms as Christian praise -- Psalm 90 : the voice of chastened wisdom -- Psalm 91 : the Messiah's invulnerability and invincibility -- Psalm 92 : you are on high forever, I AM! -- Psalm 93 : I AM's throne and the earth stand firm -- Psalm 95 : venite -- Psalm 96 : the king comes to establish justice -- Psalm 97 : his chariots of wrath the deep thunderclouds form -- Psalm 98 : a divine warrior victory song -- Psalm 99 : holy is he -- Psalm 100 : jubilate deo -- Psalm 103 : praise, my soul, the king of Heaven -- Psalm 104 : a very great God.
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Praise -- Biblical teaching; Criticism, interpretation, etc